Some modern aspects of the theory of impulsive differential equations - Perestyuk, N. A.; Chernikova, O. S. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We give a brief survey of the main results obtained in recent years in the theory of impulsive differential equations.